High-performance fiber-shaped supercapacitors using carbon fiber thread (CFT)@polyanilne and functionalized CFT electrodes for wearable/stretchable electronics. (January 2015) - Jin, Huanyu; Zhou, Limin; Mak, Chee Leung; Huang, Haitao; Tang, Wing Man; Chan, Helen Lai Wa
Abstract: Fiber-shaped supercapacitor (FSC) is a promising energy storage device for wearable/stretchable electronics by virtue of its unique features such as high flexibility, knittability, small-size and lightweight. However, the energy density of most FSC devices is limited by the relatively low operating voltage. Herein, we develop a solid-state asymmetric fiber-shaped supercapacitor made of carbon fiber thread@polyaniline and functionalized carbon fiber thread electrodes with high operating voltage (1.6 V). The as-prepared device shows a volumetric energy density up to 2 mWh cm −3 which is higher than/compatible to most reported FSCs. The maximum power density of the device is 11 W cm −3, which is comparable to typical commercial supercapacitors. Other than good rate capability, long cycle life and high volumetric capacitance, the proposed device has excellent flexibility. It can be embedded in a glove using a traditional weaving technology without degrading its capacitive performance at various bending conditions. To demonstrate the potential of our supercapacitor for stretchable electronics, we incorporate the device into a conventional elastic thread to form a stretchable supercapacitor. The capacitance of the stretchable device is well maintained even after stretching up to 100%, demonstrating its excellent stretchability. These promising results demonstrate the proposed supercapacitor has great potential as an efficient storage device for flexible and wearable electronics applications. Graphical abstract: Highlights: A flexible asymmetric fiber-shaped supercapacitor (FASC) has been developed successfully. PANI was coated on carbon fiber thread (CFT) as positive electrode and functionalized CFT was used as a negative electrode. By virtue of enlarged operating voltage (1.6 V), the as-prepared device could achieve a high energy density of 2 mWh cm −3 and power density of 11 W cm −3 . When being knitted into conventional textile and elastic thread, the FASC can be flexed and stretched repeatedly without sacrificing its capacitance.